MOF‐Derived Fe7S8 Nanoparticles/N‐Doped Carbon Nanofibers as an Ultra‐Stable Anode for Sodium‐Ion Batteries - Wang, Yu; Wen, Zi; Wang, Chang Chun; Yang, Chun Cheng; Jiang, Qing (Small (Weinheim an der Bergstrasse, Germany), 2021)
Sodium‐ion batteries (SIBs) have aroused wide concern due to their potential applications in large‐scale energy‐storage systems. In this work, a hybrid of Fe7S8 nanoparticles/N‐doped carbon nanofibers (Fe7S8/N‐CNFs) is designed and synthesized via electrospinning. As an anode for SIBs, Fe7S8/N‐CNFs exhibit a high reversible capacity of 649.9 mAh g−1 at 0.2 A g−1 after 100 cycles, and superior cycling stability for 2000 cycles at 1 A g−1 with only 0.00302% capacity decay per cycle. Such excellent performance originates from: i) Fe7S8 nanoparticles (average diameter of 17 nm), which shorten the Na+ diffusion distance; ii) the unique 3D N‐CNFs, which enhance the conductivity, alleviate the self‐agglomeration and large volume change of Fe7S8 nanoparticles, and offer numerous active sites for Na+ adsorption and paths for electrolyte diffusion. The fascinating structure and superior electrochemical properties of Fe7S8/N‐CNFs shed light on developing high‐performance SIBs anode materials. A hybrid of metal‐organic framework‐derived Fe7S8 nanoparticles/N‐doped carbon nanofibers (Fe7S8/N‐CNFs) is constructed via electrospinning and sulfuration. Owing to the synergistic effect of Fe7S8 nanoparticles and carbon network, Fe7S8/N‐CNFs exhibit superior cycling stability for 2000 cycles at 1 A g−1 with only 0.00302% decay per cycle as an anode material in sodium‐ion batteries.